Effects of COVID-19 on the quality of health care services in Colombia: a literature review - Gutiérrez-Toro , Carol Juliet; Noreña-Herrera, Camilo (Universidad y Salud, 2024)
Introduction: The COVID-19 pandemic has significantly affected the quality of health care services. Objective: To analyze the effects of COVID-19 on the quality of health care services focused on treating diseases other than COVID-19 in Colombia during the 2020-2022 period. Materials and methods: 24 articles were analyzed, which included some studies focused on national issues and others specific to the departments of Antioquia, Cordoba, Santander, and Cundinamarca. Results: The COVID-19 pandemic affected the quality of health services caring for diseases such as cancer, strokes, and critical circumstances like voluntary termination of pregnancy. Conclusion: All dimensions of health care were affected during the pandemic, especially impacting populations with chronic diseases and diseases related to child and maternal health. It is important to highlight that telemedicine and home care contributed to improving the quality of health in Colombia.